(untitled) (Research, Society and Development, 2020)
Industrial activity has intensified, significantly increasing the consumption of natural resources. Associated with intense production activity is the production of residues with different physical, chemical and toxic characteristics. The development of waste reuse technologies for other activities, mainly agriculture, which consumes a large volume of inputs, is one of the ways to reduce the environmental impact and add value to the industry. This work aimed to evaluate two products originating from industrial residues in the development of corn (Zea mays L.) and beans (Phaseolus vulgaris L.) plants. It used two materials developed from residues: the Ecogypsum used individually and associated with the Calcium Chloride (CaCl2) in the proportion 10:1. Two substrates with 25% and 75% clay were used. The Ecogypsum+CaCl2 dosages evaluated were 0, 1, 3, 5 and 7 tons.ha-1 and 1 and 3 tons.ha-1 with pure Ecogypsum. After preparing the substrates, corn and beans were sown. Plants were collected 30 days after germination and dry weight was evaluated. The corn plants responded positively to the applications of Ecogypsum + CaCl2 up to the dosage of 4.0 tons.ha-1, with the performance of the plants decreasing after this dose. In relation to the bean culture, the plants showed less significant responses in their development. The crops showed better performance in the substrate with less clay content. Regarding Ecogypsum combined with CaCl2, corn responded better to the presence of CaCl2 in the lowest dose (1.0 ton.ha-1) and beans in the highest (3.0 tons.ha-1) when compared to pure Ecogypsum .